Pergaulan Bebas dan Hamil Pranikah - Farida Farida (Analisa: Journal of Social Science and Religion, 2009)
Married by accident cases or pragnancy outside marriage boundages and freeintercourse are blur pictures of our youth generation. In addition to break religious,social, and ethical norms, those acts also ruine their own futures. These cases happenusually because of lack of youth abilities to screen, to select and to choose positiverelationship. In addition, this is because of their unstable emotion, lack of partens’monitoring and less in religious knowledges. To prevent married by accident casesand effects of free intercourse, it is advisable for every families to strengthen faithof their family mambers, to build harmonious communication with the teenagers, toimprove diciplines in family circles, to control educatively and to direct the teenagersin performing positive activities, and to give sex education wisely and proportionally.Furthermore, schools and societies are expected to contribute in monitoring theteenagers so they are not cought up in free intercourse.Key Words: Married By Accident, Intercouse, Teenager, Religion